Gastric intestinal metaplasia in a dog - Tuğçe Baş; Gülsüm Boran Çayırlı; Mahmut Ok; Mustafa Arıcan (Eurasian Journal of Veterinary Sciences)
Aim: The material of the case was a 12-year-old male Maltese Terrier dog who came to the veterinary faculty animal hospital with complaints of loss of appetite, stagnation, weight loss, intermittent diarrhea and vomiting that did not respond to treatment for 6 months. Intestinal metaplasia was diagnosed as a result of clinical examination, laboratory analysis, ultrasound examination, endoscopic examination, radiological examination, experimental laparotomy and histopathological examination. As a medical treatment for the dog; chronic gastritis treatment was applied. For this purpose, intravenous 0.9% NaCl and 5% dextrose solutions, vitamins and amino acids, maropitant, ranitidine, sucralfate, and Ceftriaxone were used for 2 weeks. It was observed that there was no response to the medical treatment applied for 2 weeks and was referred to the operation. A 1-1.5 cm biopsy material was taken from the pyloric antrum. Intestinal metaplasia was diagnosed as a result of histopathological examination of the biopsy specimen taken. After the operative intervention, oral food intake was prevented and parenteral feeding was given for 10 days. It was observed that the same symptoms continued to decrease on the 30th day of the post-operative period. Gastric intestinal metaplasia was found to be effective in chronic vomiting of dogs that did not respond to treatment. Although endoscopic examination made a significant contribution to the diagnosis of the disease, it was concluded that histopathological examination was more reliable in the type and etiology of the lesion.